2019
DOI: 10.1021/acs.energyfuels.9b01291
|View full text |Cite
|
Sign up to set email alerts
|

Layer Formation on Feldspar Bed Particles during Indirect Gasification of Wood. 1. K-Feldspar

Abstract: The choice of bed material for biomass gasification plays a crucial role for the overall efficiency of the process. Olivine is the material conventionally used for biomass gasification due to the observed activity of olivine toward cracking of unwanted tars. Despite its catalytic activity, olivine contains high levels of chromium, which complicates the deposition of used bed material. Feldspar has shown the same activity as olivine when used as a bed material in biomass gasification. As opposed to olivine, fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
(98 reference statements)
3
19
0
Order By: Relevance
“…Experimental campaigns using the same alkali-feldspar as bed material in DFB steam gasification further supported the catalytic activity observed before [37]. Faust et al [38] and Hannl et al [39] extensively studied the layer formation of alkali-feldspars obtained from DFB steam gasification experiments in a two-part study focusing on two separate feldspars, namely part 1, K-feldspar [38] and part 2, Na-feldspar [39]. While both feldspars formed a calcium-rich outer layer, an additional potassium-rich inner layer formed only on Na-feldspar particles.…”
Section: Introductionsupporting
confidence: 76%
“…Experimental campaigns using the same alkali-feldspar as bed material in DFB steam gasification further supported the catalytic activity observed before [37]. Faust et al [38] and Hannl et al [39] extensively studied the layer formation of alkali-feldspars obtained from DFB steam gasification experiments in a two-part study focusing on two separate feldspars, namely part 1, K-feldspar [38] and part 2, Na-feldspar [39]. While both feldspars formed a calcium-rich outer layer, an additional potassium-rich inner layer formed only on Na-feldspar particles.…”
Section: Introductionsupporting
confidence: 76%
“…Recent research has focused on the application of alkali feldspar ((Na,K)­AlSi 3 O 8 ) as an alternative to olivine. Feldspar has been found to show activity similar to that of olivine toward tar reduction. , Berguerand et al reported increased catalytic activity during prolonged ash interaction while at the same time the material withheld its resistance toward agglomeration, similar to the case of olivine. The interaction of woody biomass ash and alkali feldspar was described by Hannl et al and Faust et al , The authors found a transition of the Na feldspar to K feldspar and the formation of an ash layer rich in CaSiO 3 and (Na,K)­AlSiO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has focused on the application of alkali feldspar ((Na,K)­AlSi 3 O 8 ) as an alternative to olivine. Feldspar has been found to show activity similar to that of olivine toward tar reduction. , Berguerand et al reported increased catalytic activity during prolonged ash interaction while at the same time the material withheld its resistance toward agglomeration, similar to the case of olivine. The interaction of woody biomass ash and alkali feldspar was described by Hannl et al and Faust et al , The authors found a transition of the Na feldspar to K feldspar and the formation of an ash layer rich in CaSiO 3 and (Na,K)­AlSiO 4 . Wagner et al investigated the interaction of K feldspar with fuel rich in phosphorus and found a change in ash chemistry toward phosphates instead of silicates which improved the melting resistance of K feldspar.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the operating temperature to minimize the deleterious impact of tar on the operation will, therefore, be a balance between the amount of tar and the tar composition. The reactions that involve tar and precursors thereof can be affected by the use of catalytic materials or by the interaction of the bed material with the fuel ash, leading to the development of catalytic activity. Nevertheless, the materials that catalyze the tar reactions will also likely affect the reforming and cracking reactions of light hydrocarbons, and they can also catalyze the WGS reaction. As noted in the previous paragraph, this will result in an increase in the heat demand of the process.…”
Section: Descriptions Of the Dfb Gasification Configurationsmentioning
confidence: 99%